Comparison of fetal and neonatal sonographic measurements of ventricular size in second‐ and third‐trimester fetuses with or without ventriculomegaly: cross‐sectional three‐dimensional ultrasound study. (1st December 2022) - Gerbino, M.; Parodi, S.; Ballarini, M.; Paladini, D.
Abstract: Objectives: To assess, in a population comprising normal fetuses and fetuses with primary or post‐hemorrhagic ventriculomegaly, the reproducibility of measurement of neonatal ultrasound indices in the fetus and to compare the performance of various cut‐offs of these parameters to diagnose ventriculomegaly and classify its severity. Methods: This was a retrospective cross‐sectional study including 182 singleton fetuses assessed by transvaginal neurosonography. The sample populations included 116 normal fetuses and 66 fetuses with primary ( n  = 56) or post‐hemorrhagic ( n  = 10) ventriculomegaly. In all cases, the atrial width (AW) was measured according to standard protocols and the findings were compared with four sonographic indices developed in the neonate: the anterior horn width (AHW), the ventricular index (VI), the thalamo‐occipital distance (TOD) and the fronto‐occipital horn ratio (FOHR). Reproducibility of measurements was assessed using the intraclass correlation coefficient (ICC) and diagnostic accuracy of the neonatal indices was assessed against AW using areas under the receiver‐operating‐characteristics curves (AUC). Results: The intra‐ and interoperator reproducibility of measurement of AW and the neonatal measurements was excellent, with ICCs > 0.99 for all measures. The association in the fetus of all four variables developed in the neonate with the degree of ventriculomegaly as defined by the AW was strong for severe ventriculomegaly (AW > 15.0 mm; all AUC > 0.95), whereas the separation of cases with mild ventriculomegaly (AW, 10.0–15.0 mm) from those with normal AW (< 10.0 mm) was less effective. Conclusions: When applied in the fetus, all four indices of ventriculomegaly developed in neonates (AHW, VI, TOD, FOHR) were associated strongly with fetal AW when the AW measurement indicated severe fetal ventriculomegaly. However, for mild ventriculomegaly, the association was weaker, probably due to the fact that, in the fetus, mild ventriculomegaly is not caused by obstruction of the ventricular system. Considering the similar performance of the four neonatal variables and the technical issues involved in determination of TOD and FOHR in the fetus, use of VI and AHW is preferred. © 2022 International Society of Ultrasound in Obstetrics and Gynecology.